MAKNA DUKUNGAN SUAMI DALAM KEPATUHAN IBU HAMIL TERHADAP KONSUMSI TABLET ZAT BESI DI BPM SM SINGGOSARI - Siswati, Eny; Masyayih, Warda Anil; Kristiana, Ike; Fatmawati, Istiadah (LPPM STIKES HUSADA JOMBANG, 2025)
Background: Iron (Fe) is an essential micronutrient involved in hemoglobin synthesis, playing a significant role in maternal health during pregnancy. Compliance with iron tablet consumption remains a challenge, often influenced by various psychosocial factors. Among them, husband support is believed to have a strong influence on pregnant women's adherence to iron supplementation. Objectives: This study aimed to explore the meaning of husband support in enhancing pregnant women’s adherence to iron tablet consumption at BPM SM Singgosari, Jabon Village, Jombang. Methods: A qualitative phenomenological approach was employed to gain in-depth insights into the experiences of pregnant women. Data were collected through in-depth interviews, observations, and documentation involving pregnant women attending antenatal care at the midwifery clinic. Thematic analysis was used to identify emerging patterns and meanings from the participants’ narratives. Results: The findings revealed that husband support not only functioned as motivational encouragement but also had emotional and social dimensions that significantly influenced the readiness of pregnant women to follow medical recommendations. Acts of support included reminding of consumption schedules, providing emotional comfort, and accompanying antenatal visits. Such involvement fostered a stronger understanding and compliance with iron supplementation. Conclusion: The study highlights the critical role of husband support in promoting iron tablet adherence among pregnant women. The findings suggest the need for health interventions that actively involve partners, emphasizing a family-based educational approach to improve maternal nutrition outcomes.